CH3NH3PbI3 films prepared by combining 1- and 2-step deposition: how crystal growth conditions affect properties. Issue 10 (24th February 2017) - Mokhtar, Muhamad Z.; Chen, Mu; Whittaker, Eric; Hamilton, Bruce; Aristidou, Nicholas; Ramadan, Simko; Gholinia, Ali; Haque, Saif A.; O'Brien, Paul; Saunders, Brian R.
Abstract : The growth of CH3 NH3 PbI3 films is transformed using a new combined one-step and two-step deposition method which results in controlled morphology and property changes. Abstract : Perovskite solar cells continue to attract strong attention because of their unprecedented rate of power conversion efficiency increase. CH3 NH3 PbI3 (MAPbI3 ) is the most widely studied perovskite. Typically one-step (1-s) or two-step (2-s) deposition methods are used to prepare MAPbI3 films. Here, we investigate a new MAPbI3 film formation method that combines 1-s and 2-s deposition (termed 1 & 2-s) and uses systematic variation of the stoichiometric mole ratio ( x ) for the PbI2 + x MAI solutions employed. The PbI2 + x MAI solutions were used to deposit precursor films that were subsequently dipped in MAI solution as a second step to produce the final MAPbI3 films. The morphologies of the 1 & 2-s MAPbI3 films consisted of three crystal types: tree-like microcrystals (≫1 μm), cuboid meso-crystals (∼0.1–1 μm) and nanocrystals (∼50–80 nm). Each crystal type and their proportions were controlled by the value for x . The new 1 & 2-s deposition method produced MAPbI3 films with tuneable optoelectronic properties that were related to those for the conventional 1-s and 2-s films. However, the 1 & 2-s film properties were not simply a combination of those for the 1-s and 2-s films. The 1 & 2-s films showed enhanced light scattering and the photoluminescence spectra displayed a morphologically-dependent red-shift. The unique morphologies for the 1 & 2-s films also strongly influenced PbI2 conversion, power conversion efficiency, hysteresis and recombination. The trends for the performance parameters and hysteresis were compared for devices constructed using spiro-MeOTAD and P3HT and were similar. The 1 & 2-s method should apply to other perovskite formulations and the new insights concerning MAPbI3 crystal growth conditions, morphology and material properties established in this study should also be transferable.